OSTEOSARKOMA - Loho, Lily L. (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: Osteosarkoma is defined as a neoplasma in which the osteoid tissue is synthesized by malignant cells. It belongs to the most frequent nonhemapoietic skeletal malignancy with a bimodal age distribution. The causes are still unknown, however, a variety of agents and diseases are related to the development of this disease. Early signs and symptoms are not specific, mostly manifests as pain with or without palpable mass. Around 5-10% of cases undergone pathological fractures. Most osteosarcoma tumor develop in the distal part of femur in the metaphysis. Hematogen metastasis often occurs at the early stage of this disease mostly to lungs and bones. Radiological examination is important in early evaluation of osteosarcoma. Morphologically, there are several types of osteosarcoma. The most frequent type is osteosarcoma in the long bone metaphysis, primary, intramedullary, with high gradation of osteoblasts. Macroscopically, it manifests as a big, sandy, whitish grey tumor, which is often with bleeding areas and cysts; meanwhile, microscopically it varies. Malignant osteoblasts that produce osteoid matrix is the diagnostic tool. The prognosis of such cases depends on the tumor size, necrosis degree, dissemination to cortex and soft tissue, and metastasis. A teenager with a painful mass around the knee has to undergo further examination for early detection of osteosarcoma.Keywords: osteosarcoma, osteoblastAbstrak: Osteosarkoma didefinisikan sebagai suatu neoplasma dimana jaringan osteoid disintesis oleh sel ganas. Penyakit ini termasuk keganasan sistem skeletal nonhematopoetik yang tersering dengan distribusi usia bimodal. Penyebab osteosarkoma tidak diketahui, namun berbagai agen dan status penyakit dihubungkan dengan perkembangan penyakit ini. Gejala awal tidak spesifik yaitu nyeri dengan atau tanpa teraba massa. Sekitar 5-10% kasus mengalami fraktur patologik. Umumnya tumor tumbuh pada distal femur di bagian metafisis. Penyebaran hematogen sering terjadi pada awal penyakit, biasanya ke paru-paru dan tulang. Pemeriksaan radiologik berperan penting dalam evaluasi awal osteosarkoma. Secara morfologik terdapat beberapa jenis osteosarkoma, yang tersering ialah osteosarkoma pada metafisis tulang panjang, primer, intrameduler, dengan osteoblas bergradasi tinggi. Gambaran makroskopik yaitu tumor besar, berpasir, berwarna abu-abu keputihan, dan sering terdapat area perdarahan dan kiste sedangkan gambaran mikroskopik bervariasi. Osteoblas maligna yang memroduksi matriks osteoid merupakan gambaran diagnostik. Prognosis penyakit ini dipengaruhi oleh ukuran tumor, derajat nekrosis, penyebaran ke korteks dan jaringan lunak, serta adanya metastasis. Pada kasus usia belasan dengan massa yang nyeri di sekitar lutut perlu dilakukan pemeriksaan lanjut untuk deteksi dini osteosarkoma.Kata kunci: osteosarkoma, osteoblas